The Effect Of The Strategy Of Gradual Activities Difficulty In Acquiring Concepts Among Fourth Grade Students In Mathematics - Khazaal Mohammed, Galib; Abdulameer Al-Mulla, Ban Amer (Opción, 2019)
The current research aimed to identify the effect of using strategy of grad- ual activities Difficulty in acquiring concepts among fourth grade students in mathematics, and to achieve the target of research and developed the null hypothesis that assumes the lack of statistically significant differences between the experimental group that will study the using strategy of gradual activities Difficulty and the control group , which will be examined in the usual way in teaching , research sample consisted of (60) student researcher Achtarthn Qsidia of the study population into two groups by distributors (30 ) students in the experimental group and 30 students in the control group , the researcher has Kavit between these two groups in the number of variables (Age meas- ured in months , and collection former mathematics , and IQ test , and prior knowledge in mathematics ) , have been prepared researcher tested for the acquisition of mathematical concepts consisting of (36) paragraph of type se- lection of multi were verified sincerity and persistence and effectiveness of alternatives wrong , and after application the sample and analyze the results statistically significant results revealed the superiority of the experimental group that learned of using strategy of gradual activities Difficulty in the ac- quisition of mathematical concepts in the light of the findings and conclusions of the researcher presented a number of recommendations and proposals, in- cluding the use of a specimen (of using strategy of gradual activities Difficulty) in teaching being in line with modern educational theories that emphasize the participation of female actors in the process of learning and education, and because of its impact on Ntaújhen by on the other hand to build a spirit of cooperation and competition among them , a similar study of the current study with other variables not addressed by the present study (such trends , the ability to solve problems , develop curiosity)